Pattern - Kiely, Orla. (London : Conran Octopus ; New York : Distributed in the U.S. by Hachette Book Group, 2010)
The world of Orla Kiely is one where pattern reigns. Giving a personal account of what informs her work and inspires her designs, Orla looks at pattern in all its manifestations - the impact of scale and proportions, rhythm and texture, and the all-important dimension of colour.
Includes index.
boek
Keywords: Kiely, Orla -- Themes, motives